Effectiveness of Implementation and Learning Management Strategies in Improving Santri Learning Achievement - Afifah Hidayati; Muhammad Yusuf Firdausi; Jalaludin (Journal of Asian Primary Education (JoAPE), 2025)
This study aims to confirm the effectiveness of learning management strategies in improving students' learning achievement at Darussalam Buntet Islamic Boarding School. Using a descriptive qualitative approach, data were collected through in-depth interviews, direct observation, and documentation studies of learning activities at various levels of dirosah classes. The results showed that the learning strategies applied by teachers, such as the use of yellow books according to level, sorogan and bandongan methods, and active deliberation proved successful in creating a conducive learning atmosphere and increasing santri involvement in the learning process. Teachers do not only act as material deliverers, but also as facilitators who encourage active participation, provoke santri ideas, and reward their achievements. The implementation of this strategy is proven to improve memorization, understanding of the material, and the ability of students to retell lessons independently. Learning evaluations are carried out periodically to measure santri achievements and improve the methods used. Obstacles such as the low motivation of some students are overcome through a disciplinary approach, strengthening communication, and emotional support from the board. This study confirms that structured and adaptive learning management can significantly improve students' learning achievement. This finding makes an important contribution to the development of a pesantren education system that is more effective and responsive to the needs of students.